Nursing students’ perceptions of learning in the clinical environments at a private nursing institution in Gauteng - Padayachee, Reshola (My University, 2024)
The clinical learning environment is a complex entity and forms an essential part in the students’ training and professional socialization. Nursing students spend a considerable part of their training in the clinical environment where they develop their competence in nursing procedures and nursing skills. The clinical environment has many benefits, specifically in meeting the learning objectives of the students and to prepare them to function independently once they qualify . However, previous studies have shown that it can be very challenging and stressful for the student and can compromise them from becoming safe practitioners who ensure safe patient outcomes as aimed for during their training. Purpose/Aim The aim of this study was to explore the perceptions of nursing students about learning in the clinical environment and to provide recommendations to the Nursing Education Institution (NEI) on how to address these perceptions of the students. Method The study adopted a qualitative descriptive design using semi - structured interviews to answer the research question. Data analysis Thematic analysis was used to analyse the data. The data was then organised and understood and before codes were assigned using words and phrases from the data. The themes and subthemes that were derived, was linked to the research questions and the object ives of the study. Setting Data was collected at a purposively selected Private Nursing Education Institution in Gauteng. Main Findings Overall, students have positive experiences in the clinical environments. Support exists but needs to be reinforced by all. There is adequate resources and exposure in the clinical environment. Challenges that require attention are language and communication, and a more cooperative relationship from nursing staff to ensure that the clinical environment is conducive, and that learning takes place.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Nursing to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg , 2023
Keywords: Nursing students; Private nursing education institution